Insights into the genetic characteristics, clustering patterns, and phylogeographic dynamics of the JC polyomavirus, 1993 to 2023 - Shah, Pir Tariq; Ejaz, Mohammad; Tamanna, Kosar; Riaz, Muhammad Nasir; Wu, Zhenyong; Wu, Chengjun (Virus research, 2024)
•This study describes the genetic characteristics, clustering patterns, and phylogeographic dynamics of the JC polyomavirus (JCV) from 1993 to 2023.•All the available complete genomes (n = 656), VP1 (n = 1547), and large t antigen (n = 724) isolated globally were investigated.•All the JCV strains are classified into four major phylogenetic clades, i.e., GI-GIV, where GI is further grouped into two types (GI.1 and GI.2), each with five sub-clades (GI.1/2 a-e), GII into three (GII a-c), GIII as a separate clade, and GIV into seven sub-clades (GIV a-g).•The phylogeographic network analysis indicated four major clusters corresponding to GI-GIV clades, each with multiple subclusters and mutational sub-branches corresponding to the subclades.•Genetic recombination analysis identified an inter-genotype recombinant within the NCCR region, while the amino acid variability analysis revealed high entropy across all proteins.•The study provides a comprehensive classification, distribution, and genetic variability patterns of JCV strains during 1993 to 2023. The human JC polyomavirus (JCV) is a widespread, neurotropic, opportunistic pathogen responsible for progressive multifocal leukoencephalopathy (PML) as well as other diseases in immunosuppressed individuals, including granule cell neuronopathy, JCV-associated nephropathy, encephalitis, and meningitis in rare cases. JCV classification is still unclear, where the ICTV (International Committee on Taxonomy of Viruses) has grouped all the strains into human polyomavirus 2, with no classification on clade and subclade levels. Therefore, JCV strains were previously classified using different genomic regions, e.g., full-length, VP1, and the V-T intergenic region etc., and the strains were grouped into several types related to various geographic locations and human ethnicities. However, neither of these classifications and nomenclature contemplates all the groups described so far. Herein, we evaluated all the available full-length coding genomes, VP1, and large T antigen nucleotide sequences of JCV reported during 1993–2023 and classified them into four major phylogenetic clades, i.e., GI-GIV, where GI is further grouped into two types GI.1 and GI.2 with five sub-clades each (GI.1/GI.2 a-e), GII into three (GII a-c), GIII as a separate clade, and GIV into seven sub-clades (GIV a-g). Similarly, the phylogeographic network analysis indicated four major clusters corresponding to GI-GIV clades, each with multiple subclusters and mutational sub-branches corresponding to the subclades. GI and GIV clusters are connected via GI.1-e reported from Europe and America, GII, GIII and GIV clusters are connected by GII-b and GII-c strains reported from Africa, while GIV cluster strains are connected to the Russia-Italy JCV haplotype. Furthermore, we identified JCV-variant-GS/B-Germany-1997 (GenBank ID: AF004350.1) as an inter-genotype recombinant having major and minor parents in the GI.1-e and GII-a clades, respectively. Additionally, the amino acid variability analysis revealed high entropy across all proteins. The large T antigen exhibited the highest variability, while the small t antigen showed the lowest variability. Our phylogenetic and phylogeographic analyses provide a new approach to genotyping and sub-genotyping and present a comprehensive classification system of JCV strains based on their genetic characteristics and geographic distribution, while the genetic recombination and amino acid variability can help identify pathogenicity and develop effective preventive and control measures against JCV infections.